2019
DOI: 10.1039/c9lc00080a
|View full text |Cite
|
Sign up to set email alerts
|

Inertial focusing with sub-micron resolution for separation of bacteria

Abstract: Inertial focusing in curved channels is demonstrated for particles between 0.5 and 2.0 μm in diameter; a range of biological relevance since it comprises a multitude of bacteria and organelles of eukaryotic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 41 publications
2
47
0
Order By: Relevance
“…In another study 43 A threshold Reynold's number was found for each particle size, at which, microparticles will be trapped inside a laminar microvortex. As the desired particle size decreases, the forces affecting it decreases drastically as Cruz et al 44 described when aiming to focus particles as small as 1 mm. Therefore, when aiming to focus smaller particles (less than 5 mm), this force reduction has to be compensated by increasing the ow rate or by decreasing the channel dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…In another study 43 A threshold Reynold's number was found for each particle size, at which, microparticles will be trapped inside a laminar microvortex. As the desired particle size decreases, the forces affecting it decreases drastically as Cruz et al 44 described when aiming to focus particles as small as 1 mm. Therefore, when aiming to focus smaller particles (less than 5 mm), this force reduction has to be compensated by increasing the ow rate or by decreasing the channel dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…With a laser-induced fluorescence module integrated, the on-chip flow cytometer system could offer a high detection throughput of 2100 particles/s. Moreover, using the adjusted curved spiral microchannel, Cruz et al realized ultrasensitive submicro particle focusing [48]. Particles with size between 0.5 µm to 2.0 µm could be aligned on corresponding equilibrium positions at the end of the microchannel.…”
Section: Spiral Microchannelmentioning
confidence: 99%
“…(1) Main Straight Channel for Inertial Migration Effect The main straight channel with rectangular cross sections is located in the entrance, and connects the curve channels. As Poiseuille flow naturally presents in the microchannels, particles/cells usually are acted upon by two fluid dynamic effects-wall-induced lift forces and shear-gradient lift forces-for their discrete equilibrium positions [33,34]. The wall-induced lift forces push the particles/cells away from the walls, while the shear-gradient lift forces push the particles/cells towards the walls [35].…”
Section: Device Design and Working Principlementioning
confidence: 99%